PERKEMBANGAN GERAKAN SAREKAT ISLAM DALAM KONTEKS PERJUANGAN SOSIAL POLITIK DI INDONESIA 1912-1921 - Muhammad Adi Saputra; Agus Junaedi; Anny Wahyuni (Universitas Sultan Ageng Tirtayasa, 2023)
This research examines the development of the Sarekat Islam (SI) movement in the context of the socio-political struggle in Indonesia in 1912-1921. SI is a socio-political movement that fights for the rights of workers and peasants and strengthens Islamic teachings in Indonesia. This research examines the factors that prompted the emergence of the SI movement, as well as the turmoil of the IS organization's journey in Indonesia, including complex internal and external conflicts. This research shows that SI was an important socio-political movement in the socio-political struggle in Indonesia in the early 20th century. This movement succeeded in fighting for the rights of workers and peasants, as well as strengthening Islamic teachings in Indonesia. Despite experiencing complex internal and external conflicts, SI has managed to maintain its existence and expand its mass base and develop its political wings. This makes SI an important political force in the socio-political struggle in Indonesia.